Mechanobiological Adaptation to Hyperosmolarity Enhances Barrier Function in Human Vascular Microphysiological System - Joon Ho Kang; Minjeong Jang; Su Jin Seo; Andrew Choi; Daeeun Shin; Suyoung Seo; Soo Hyun Lee; Hong Nam Kim (Advanced Science, 2023)
Abstract In infectious disease such as sepsis and COVID‐19, blood vessel leakage treatment is critical to prevent fatal progression into multi‐organ failure and ultimately death, but the existing effective therapeutic modalities that improve vascular barrier function are limited. Here, this study reports that osmolarity modulation can significantly improve vascular barrier function, even in an inflammatory condition. 3D human vascular microphysiological systems and automated permeability quantification processes for high‐throughput analysis of vascular barrier function are utilized. Vascular barrier function is enhanced by >7‐folds with 24–48 h hyperosmotic exposure (time window of emergency care; >500 mOsm L−1) but is disrupted after hypo‐osmotic exposure (<200 mOsm L−1). By integrating genetic and protein level analysis, it is shown that hyperosmolarity upregulates vascular endothelial‐cadherin, cortical F‐actin, and cell–cell junction tension, indicating that hyperosmotic adaptation mechanically stabilizes the vascular barrier. Importantly, improved vascular barrier function following hyperosmotic exposure is maintained even after chronic exposure to proinflammatory cytokines and iso‐osmotic recovery via Yes‐associated protein signaling pathways. This study suggests that osmolarity modulation may be a unique therapeutic strategy to proactively prevent infectious disease progression into severe stages via vascular barrier function protection.